Lumbar puncture - Dannandeh, F (Iran University of Medical Sciences, 1995)
Lumbar puncture is one of the most common methods for assessment of central nervous system. Allen is illustrating the role of nurses in relation to probable fears about this technique. Question: what is lumbar puncture? Answer: this technique is proper method that one needle and trocar enter to subarachnoid space in lumbar spine. This method is most common diagnostic test for central nervous system. Question: what is the goal of lumbar puncture? Answer: diagnostic goals are: a) attaining of one sample of CSF for laboratory analysis b) measuring of lumbar CSF pressure c) contrast injection for radiologic diagnosis. Therapeutic goals are: a) direct drug injection in subarachnoid space (Intrathecal) b) extracting of CSF for decreasing of intracerebral pressure (ICP).